Echocardiographic Evaluation of Malabari Goats with Haemoparasitic Diseases - Tejaswini, K. G.; Unny, Madhavan; Pillai, Usha Narayana; Ajithkumar, S.; Thirupathy Venkatachalapathy; Sunanda, C. (International Journal of Livestock Research, 2020)
The study was carried out to assess the echocardiographic changes in Malabari goats with haemoparasitic diseases. Twelve female Malabari goats presented to the University Veterinary Hospital which were positive for blood parasites were taken up for the study. Out of twelve animals, nine were positive for Anaplasma spp, two were positive for Theileria spp and one animal was positive for both Anaplasma and Theleria infection. Pericardial effusion was recorded in one goat. Hyperechoic spots were recorded in the left ventricle in two goats. The values of the parameters studied are reported.